Novel Aceclofenac-L-Cystine and Aceclofenac-Urea Cocrystals with Enhanced Oral Bioavailability - Kumar, Saroj; Gupta, Amresh; Mishra, Chanchal K.; Singh, Satyawan (Current Drug Delivery, 2021)
Aim: Present research work focuses on the improvement of biopharmaceutical properties of aceclofenac (ACF) by the cocrystal approach. Background: ACF is one of the frequently used Nonsteroidal Anti-Inflammatory Drugs (NSAID). ACF is a BCS Class - II drug (low solubility and high permeability) with poor solubility and low oral bioavailability. Hence, the improvement in solubility and bioavailability of ACF is very crucial for successful product development. Nowadays, pharmaceutical cocrystals are considered a novel solid form of drugs. These cocrystals may have different physicochemical as well as biopharmaceutical properties as compared to the parent drug. In a previous study, the cocrystal of ACF (ACF-l-CYS NG and ACF-UREA NG) was successfully prepared and characterized. These cocrystals have shown superior solubility and dissolution rate than pure ACF in HCl buffer (pH 1.2). The synthesized cocrystals were also found non-hygroscopic and stable for 6 months under standard test settings. However, pharmacokinetic evaluation of these cocrystals has not been explored yet. Objective: The specific objective of this research work was the measurement of bioavailability and other pharmacokinetic parameters of ACF cocrystals prepared by the mechanochemical grinding method. Methods: Cocrystals of ACF with l-cystine and urea were prepared by neat grinding (NG) method and in-vivo oral bioavailability of prepared cocrystals was measured in Wistar rats. The plasma drug concentration was measured by high-performance liquid chromatography (HPLC), and the pharmacokinetic data was analyzed by “PK solver” software. Results: Percent relative bioavailability of ACF-l-CYS NG and ACF-UREA NG cocrystals in Wistar rats was found to be 242.05 ± 65.27and 178.93 ± 45.21 respectively, which were significantly higher (ANOVA, P < 0.05) than that of pure ACF. Conclusion: The present study indicates that the enhanced aqueous solubility of the prepared cocrystals leads to enhanced oral bioavailability of ACF. Thus, the cocrystals may be an alternative crystalline form of the drug that can enhance the solubility, dissolution rate, and oral bioavailability of many poorly soluble drugs.
Keywords: oral bioavailability